(untitled) (Cadernos de Sociomuseologia, 2026)
This article analyzes museums as meaning-making devices at the intersection of memory, power, and History teaching. It investigates the transition from royal collecting to the institutionalization of memory in Brazil, viewed through the lens of Bruno Brulon’s social museology. The Imperial Museum of Petrópolis is employed as a case study, understood as a site of monumental memory and a pedagogical device. The analysis demonstrates that its curatorial structure, while ratifying canonical discourses, presents fissures that allow for critical appropriation and the questioning of structural silences. The study concludes that the museum acts as an arena of symbolic dispute, fundamental for the development of a reflexive historical consciousness and the exercise of plural citizenship. Keywords: Museums; Memory; Museology; Historical consciousness.